Convergence Analysis for the SM-Iteration in Banach Spaces (Journal of Nonlinear Modeling and Analysis, 2025)
In this article, the fixed point of the SM iterative approach is approximated via Suzuki mapping. In the context of Banach spaces, we provideboth weak and strong convergence for the SM iteration. Then, by comparing itwith certain well-known iterations, we give some numerical examples to showthe effectiveness of SM iteration for the Suzuki-type mapping.